Lost magnetic moments - Korytár, Richard; Lorente, Nicolás (Nature (London), 2009)
A neat study gives clear-cut evidence that when a wire made of a magnetic material such as iron is squashed to the atomic scale, the material's magnetism disappears via an exotic physical process. Shrinking magnets: a new spin on the Kondo effect Magnetism in metals such as iron is typically considered an intrinsic property of the material. But as with many physical effects, such general pictures can break down once you reduce the size of the system to the nanoscale. Calvo et al . report a striking manifestation of such a change: they find that when the diameter of a magnetic wire is reduced to atomic dimensions, the material's magnetic properties are strongly altered, to the point where magnetism can even be eliminated. This is an unexpected realization of the so-called Kondo effect, for which one usually requires two different species of atoms; it also highlights vividly the need to take into account atomic-scale geometry when investigating the properties of magnetic nanostructures.